State trading deregulation and prairie durum wheat production - Colin Andre Carter; Shon Ferguson (Research Institute of Industrial Economics (IFN), 2019)
We estimate the impact of the 2012 removal of the Canadian Wheat Board's (CWB) single-desk on the spatial pattern of durum wheat acres in Western Canada. We analyze changes in durum seeded acres with a panel regression and Census Agricultural Region data from 2004-2016. Our results indicate that removal of the CWB single-desk had a significant impact on total durum production in Western Canada. In addition, we find that the spatial distribution of durum wheat acres shifted towards drier areas, an improvement in the efficiency of resource allocation.
Keywords: L43; Q17; Q18; R12; R14; 330; State trading enterprises; Deregulation; Agricultural regulation; Comparative advantage